Macromineral requirements for growing Saanen goat kids - Gomes, R. A. [UNESP]; Oliveira-Pascoa, D. [UNESP]; Teixeira, I. A. M. A. [UNESP]; de Medeiros, A. N.; Resende, Kleber Tomás de [UNESP]; Yanez, E. A.; Ferreira, A. C. D. (Elsevier B.V., 2011)
Understanding mineral nutritional requirements is important to providing diets that appropriately meet animals' needs. This study estimates the net requirements of calcium (Ca), phosphorus (P), magnesium (Mg), sodium (Na), and potassium (K) for growing goats. Twenty Saanen kids with initial body weights (BWs) of 5 kg were used in this experiment. of these kids, five were slaughtered at the beginning of the experiment, representing the initial body weight. Another six were slaughtered at BWs of 12.5 kg, and the remainder were slaughtered at BWs of 20 kg. All of the animals were fed ad libitum with a diet consisting of 50% roughage and 50% concentrate, which was formulated to meet nutritional requirements for gains of 150 g/day, except those that were slaughtered at the beginning of the experiment. The experimental design was completely randomized and used three treatments (slaughter weights). Logarithmized allometric equations were used to calculate the relationships between macromineral quantities and empty body weights (EBWs), and these relationships were observed to be highly significant (P < 0.0001). The macromineral body composition per kilogram of EBW increased from 9.9 to 10.9 g of Ca/kg EBW, 8.8 to 9.08 of P/kg EBW, and decreased from 0.78 to 0.65 g Mg/kg EBW, 2.0 to 1.1 g Na/kg EBW, and 2.7 to 1.6g K/kg EBW in Saanen kids with BWs that ranged from 5 to 20 kg. The net requirements per 100 g of gained BW decreased from 1012 to 930 mg Ca, 851 to 727 mg P, 63 to 45 mg Mg, 94 to 43 mg Na, and 147 to 74 mg K for Saanen kids with BWs that ranged from 5 to 20 kg. Differences were not observed between Ca, P and Mg net requirements in our study and those that were proposed by NRC, however Na and K net requirements for gain were lower than recommended by NRC indicating that for these minerals, this system may not be the most appropriate for the formulation of goat diets in tropical conditions. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Calcium; Goats; Magnesium; potassium; Phosphorus; requirements; Sodium